MARKETING STRATEGY THROUGH SALES CALL AND TELEMARKETING TO INCREASE ROOM REVENUE AT THE LERINA HOTEL NUSA DUA - Ni Luh Linda Astri Rinsia Dewi; Ni Nyoman Triyuni; I Nyoman Winia (Journal of Applied Sciences in Travel and Hospitality, 2018)
This research is conducted to know the indicators that become the strengths, weaknesses, opportunities and threats. The method used is descriptive qualitative with the number of respondents as many as 8 people through purposive sampling. Purposive sampling is the sampling of data sources with a specific purpose, means that the selected respondents are the people who know how the strategy will be used. Sales Call and Telemarketing are the optimum strategy used to increase room revenue. Based on effectivity and efficiency of these strategy, The Lerina Hotel Nusa Dua keep used these strategy to face client needed. The strength of The Lerina Hotel Nusa Dua is to have complete facilities, but the Weaknesses is to have merchandise that can be brought overside. The opportunities of The Lerina Hotel Nusa Dua is the secure of Bali Island as quite conducive, then the threats is the lifestyle of a growing community. The position of The Lerina Hotel Nusa Dua at present and future is in cell V or grows and stability. Being in a V cell position it is advisable to expand markets, production facilities and technologies through internal or external development through acquisitions or joint ventures with other companies in the same industry. The marketing strategies that can be applied to The Lerina Hotel Nusa Dua are Utilizing social media for promotional tools, Utilizing the Big Days of religious and local culture (Balinese) for promotion, Improving facilities owned to support event activities (MICE) such as adding amenities for meetings, and Adding some amenities that guests can take home as a souvenir. The advice given to the management is to maintain the cleanliness of the hotel and surrounding buildings, intensifying various promotions, especially in the field of Food and Beverage (F & B) and event in order to increase additional hotel revenue.